A method for simulation the effect of the reduced frequency resolution of the ear in patients with sensorineural hearing loss - M. I. Porhun; M. I. Vashkevich (Informatika)
A method for the simulation of reduced frequency resolution of the ear in patients with sensorineural hearing loss is proposed. The method is based upon the ability to adjust it according to the audiogram of a concrete person by frame-by-frame signal processing in the frequency domain. Simulation of the effect of the reduced frequency resolution of the ear is achieved by processing the components of amplitude spectrum of the original sound signal by the "smearing" function. The "smearing" function is formed from the amplitude-frequency characteristics of the auditory filters, which bandwidth is determined by the audiogram of the deaf person. The proposed method is implemented in the MATLAB. An experimental study of the effect of the reduced frequency resolution of the ear using the speech intelligibility test was conducted. The experiment involved 15 people who listened the records processed by the proposed method with various settings and noise conditions. Experimental data have shown that reduced frequency resolution of the ear leads to the deterioration in speech intelligibility, especially in the presence of background noise. Based on the answers of the participants of the experiment, the confusion tables of sounds were compiled, reflecting the fact of indistinguishability of sounds similar in frequency, that confirms the correctness of the proposed method.